Progress in the structural modification and pharmacological activity of isosteviol - Tao Wang; Bowen Pan; Lijuan Liu; Zhangchao Dong; Wenhui Zhang; Xiongwei Liu; Ying Zhou; Yang Shi (Acta Materia Medica)
Isosteviol and its derivatives, diterpene compounds with a wide range of biological activities, play important antiviral, antibacterial, antioxidant, antitumor, analgesic, anti-inflammatory, antipyretic, antifungal, and anticardiovascular disease roles. Because of its unique diterpene skeleton, isosteviol is frequently used as an active framework in drug synthesis, thus helping medicinal chemists design highly selective, potentially active, and multifunctional isosteviol analogs for the treatment of various diseases. In recent years, rapid developments in the design and synthesis of isosteviol derivatives have proven effective and important in the field of medicinal chemistry research. This article briefly reviews the novel derivatives obtained through structural modification of isosteviol, including their pharmacological activities, to provide a reference for the development of new synthetic strategies and the construction of new isosteviol derivatives, and to guide preclinical studies and development of new drugs with greater pharmacological efficacy.